Swans and lead fishing weights: a systematic review of deposition, impacts and regulations in Europe - Wood, Kevin A.; Newth, Julia L. (Wildfowl, 2024)
Lead is a potent metabolic poison that is highly toxic to all life; the World Health Organization states that there is no safe level of exposure to lead. Despite its toxicity, lead is still commonly used in some recreational activities, such as the “sinkers” and other lead weights used in fishing. Swans foraging for grit to aid digestion may ingest discarded lead weights, resulting in lead poisoning. Here, we aimed to synthesise the information currently available on lead fishing weights and swans in Europe, to inform current and future policy. We carried out a systematic review of the literature from Europe on the deposition of lead fishing weights and the impacts of lead (Pb) poisoning associated with fishing weights on swans, as well as efforts to mitigate these impacts through regulations. On screening 605 papers identified during our literature searches, we found 45 relevant papers from which information could be extracted. These indicated that the deposition of lead fishing weights resulted in accumulated densities of up to 339 sinkers m–2 with an estimated deposition rate of c. 3,000 tonnes per year within the 27 EU countries alone. Elevated lead concentrations in blood and other tissues and organs of both Mute Swans Cygnus olor and Whooper Swans Cygnus cygnus have been reported. The mean blood lead concentrations in 19 of the 20 studies conducted where lead fishing weights were used exceeded the threshold of 20 μg dL−1 that is typically considered indicative of elevated blood lead concentrations. Moreover, the maximum blood lead concentration reported in each of the 20 studies exceeded the 20 μg dL−1 threshold, with a maximum reported value of 5,134 μg dL−1. The mean kidney and liver lead concentrations estimated from our review were 642.5 μg g–1 DM and 79.3 μg g–1 DM, respectively, and elevated above background levels of 10 μg g–1 DM. Impacts of lead fishing weights on the breeding success of Mute Swans included a reduced chance of breeding successfully amongst individuals with elevated blood lead concentrations, as well as increased pre- and post-fledging cygnet mortality. Lead fishing weights have been a cause of mortality in both Mute Swans and Bewick’s Swans Cygnus columbianus bewickii, accounting for up to 70% of swan deaths in areas with recreational fishing. Evidence from the UK demonstrates that lead poisoning due to fishing weights limited Mute Swan population size, which approximately doubled after key sizes of lead fishing weights were banned in 1987. Within Europe, statutory regulations on lead fishing weights currently exist only in the United Kingdom and Denmark, with some voluntary actions to reduce and phase-out such lead use in Belgium, the Netherlands and Sweden. Proposals which would ban lead fishing weights in all 27 European Union member states are currently under consultation. Despite some progress in reducing the impacts of lead fishing weights on swans in a few countries, the available data on swan mortality and elevated Pb concentrations in tissue and organs demonstrate that lead poisoning due to fishing weights remains a major threat to swans within Europe.